Analysis of 17β‐estradiol, estriol and estrone in American eel (Anguilla rostrata) tissue samples using liquid chromatography coupled to electrospray differential ion mobility tandem mass spectrometry. (18th April 2017) - Cohen, Alejandro; Ross, Neil W.; Smith, Paul M.; Fawcett, James P.
Abstract : Rationale: 17β‐Estradiol (E2), estrone (E1) and estriol (E3) are steroid hormones responsible for the regulation of the female reproductive system. Estradiol is planned to be used to feminize eels in aquaculture in order to improve their size and marketability. The residual levels of these hormones in fish tissue must be monitored to meet the requirements of food regulatory agencies. Few studies have studied these hormones in complex biological matrices such as fish tissue. Methods: We developed a method to analyze E1, E2 and E3 in fish tissue using liquid chromatography in combination with differential ion mobility spectrometry (DMS) and tandem mass spectrometry (MS/MS). The mass spectrometer was operated in negative polarity selected reaction monitoring (SRM) mode. To test the performance of this method, residual levels of E1, E2 and E3 were measured in the muscle tissue of juvenile eels subjected to feminization treatment with E2. Results: We report that following 17β‐estradiol treatment, E2 is rapidly metabolized from the eel tissue, with a 50% depletion rate per day. Five days post‐treatment, E2 returned to the level found in non‐treated controls, similar to levels found in wild mature female eels. Conclusions: The method presented herein allows the quantitative analysis of E1, E2 and E3 in fish tissue samples. Under the experimental conditions, E2 in fish tissue samples returned to physiological levels post hormonal treatment. Copyright © 2017 John Wiley & Sons, Ltd.